2010
DOI: 10.1088/1367-2630/12/9/095019
|View full text |Cite
|
Sign up to set email alerts
|

Simulating quantum effects of cosmological expansion using a static ion trap

Abstract: We propose a new experimental testbed that uses ions in the collective ground state of a static trap for studying the analog of quantum-field effects in cosmological spacetimes, including the Gibbons-Hawking effect for a single detector in de Sitter spacetime, as well as the possibility of modeling inflationary structure formation and the entanglement signature of de Sitter spacetime. To date, proposals for using trapped ions in analog gravity experiments have simulated the effect of gravity on the field modes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 37 publications
0
40
0
Order By: Relevance
“…This idea might be experimentally challenging but it opens up a new possible way to study cosmology. The study of the analogue of cosmological particle creation with trapped ions was proposed in (Schützhold et al, 2007), and more recently, the analogue of quantum field effects in cosmological spacetimes was investigated in (Menicucci et al, 2010). There are also numerous similarities between the behavior of superfluid helium and cosmological phenomena, such as processes in the early universe, as discussed in detail in (Volovik, 2009).…”
Section: Cosmologymentioning
confidence: 99%
See 1 more Smart Citation
“…This idea might be experimentally challenging but it opens up a new possible way to study cosmology. The study of the analogue of cosmological particle creation with trapped ions was proposed in (Schützhold et al, 2007), and more recently, the analogue of quantum field effects in cosmological spacetimes was investigated in (Menicucci et al, 2010). There are also numerous similarities between the behavior of superfluid helium and cosmological phenomena, such as processes in the early universe, as discussed in detail in (Volovik, 2009).…”
Section: Cosmologymentioning
confidence: 99%
“…Unruh effect Ions (Alsing et al, 2005) Hawking radiation Atoms (Giovanazzi, 2005) Ions (Horstmann et al, 2010) Superconducting circuits (Nation et al, 2009) Universe expansion BEC (Fischer and Schützhold, 2004) Ions (Menicucci et al, 2010;Schützhold and Mostame, 2005) Atomic physics:…”
Section: Application Proposed Implementationmentioning
confidence: 99%
“…It has been suggested that a static ion trap may simulate the quantum effects of expanding universe. 38 It has also been observed that the quantum cosmology for the FRW universe minimally coupled to a massive scalar field is equivalent to a spinless charged particle in a homogeneous timedependent magnetic field along a fixed direction. 39 The infinite oscillations near the singularity can be simulated by time-dependent magnetic fields of over-critical strength.…”
Section: Resultsmentioning
confidence: 99%
“…Condensed matter physics provides a third conceptual framework, where gravity is viewed as an emergent phenomenon. Motivated by techniques and concepts native to the study of manybody interactions in condensed matter physics, this perspective has recently stimulated investigations into gravity analogues in condensed matter systems [7][8][9][10][11][12], emergent graviton excitations in qubit models [13], and quantum graphity (CDT and matrix models [14,15] may also be viewed from this perspective).…”
Section: Introductionmentioning
confidence: 99%